Glycopolymer polyelectrolyte multilayers composed of heparin and maltose-modified poly(ethylene imine) as a strong/weak polyelectrolyte system for future drug delivery coatings: Influence of pH and sugar architecture on growth of multilayers and multilayer swelling and stability - Salem, Samaa; Mueller, Martin; Torger, Bernhard; Janke, Andreas; Eichhorn, Klaus-Jochen; Voit, Brigitte; Appelhans, Dietmar (Macromolecular Chemistry and Physics, 2015)
Establishing highly sophisticated polymer films for delivery systems in a biological environment and bioanalytical tasks, the formation, thickness, swelling behavior, and (physiological) stability of highly biocompatible polyelectrolyte multilayers (PEMs) are described. These PEMs are composed of the very weak polycation maltose-modified hyperbranched poly(ethylene imine) (PEI-Mal) and the strong polyanion heparin sodium salt (HE - Na + ) deposited on Si wafer substrates . Two different glyco architectures for PEI-Mal are used, characterized by two different degrees of maltose decoration on a PEI scaffold. Using two pH-dependent deposition approaches for optimizing the (physiological) PEM stability and swelling, PEMs are characterized by (in situ) ellipsometry, atomic force microscopy (AFM), and (in situ) attenuated total reflection-Fouriertransform infrared (ATR-FTIR). Thus, PEMs reveal significantly different thicknesses, growth mechanisms (linear versus exponential), and swelling behavior in dependence of both the polycation architectures and the deposition protocol. These PEMs will allow the study of their complexation and release properties as preswollen PEMs against anionic drug molecules, especially under physiological conditions in the future.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Dendritic glycopolymers; Drug delivery coatings; Heparin; Physiological stability; Polyelectrolyte multilayers